Partisan Mortality Cycles - Daniel L. Millimet; Travis Whitacre (Institute of Labor Economics (IZA), 2025)
Geographic disparities in mortality rates in the US are pronounced and growing. The Black-White mortality gap is volatile but persistent, while the Rich-Poor mortality gap is increasing dramatically. While the causes of these inequalities are not understood, recent attention has focused on the role of place-specific factors. Here, we explore the importance of politics as a place-specific factor contributing to spatial inequality in mortality. Specifically, we test for the existence of partisan mortality cycles using panel data on counties from 1968-2016 and information on the political ideology of state and federal political officials. We confirm the existence of partisan mortality cycles, finding lower mortality in counties governed by more liberal political regimes. Several sources of heterogeneity are also uncovered. While additional research is needed, the analysis here suggests that analyses of spatial, racial, and income differences in mortality ought to start with the political system.
Keywords: I10; I18; J10; 330; mortality; ideology; geographic disparities; political cycles